New Fixed Point Results of Single-Valued Mapping for c-Distance in Cone Metric Spaces - Zaid Mohammed Fadail; Abd Ghafur Bin Ahmad; Ljiljana Paunović (Abstract and Applied Analysis)
A new concept of the c-distance in cone metric space has been introduced recently in 2011. The aim of this paper is to extend and generalize some fixed point results in literature for c-distance in cone metric spaces by replacing the constants in contractive conditions with functions. Some supporting examples are given.